Examining Score Report Language in Accountability Testing - Roduta Roberts, Mary; Gotch, Chad M.; Lester, Jessica Nina (Frontiers in Education, 2018)
The purpose of this study was to examine patterns of language use in score reports within a North American context. Using a discourse analysis approach informed by conversation analysis, we explored how language was structured to express ideas or (re-)produce values, practices, and institutions in society. A sample of ten reports from the United States and Canada within the domain of accountability testing was selected. Observed patterns of language represented micro-discourses embedded within broader discourse related to accountability mandates within each country. Three broad themes were identified within and across the score reports— Displays of Information, Knowledge Claims, and Doing Accountability. Within each of the broad themes were sub-themes—script formulations, hedging, establishing authority, establishing responsibility, word choice, and visual representations—that characterized more fine-grained textual features. Future research may explore empirical evidence for the social dynamics identified through this study’s textual analysis. Complementary lines of research on both cognitive and affective factors of score report interpretation and use are encouraged.